Media credibility, artificial intelligence and the legitimacy of journalism - seddar, rabah; touati, noureddine (Journal of Social Sciences and Humanities, 2022)
This study deals, through a theoretical approach, with the phenomenon of the credibility of information in its dimension linked to the tendency to use artificial intelligence algorithms in robot journalism, and the effects of the standardization of content values. media based on the pre-established values of the initiators of these algorithms, and what this can generate in terms of credibility, as one of the values on which the legitimacy of journalism and journalists in different societies is based, despite the differences between specialists concerning the dimensions of this credibility and its judgment in the eyes of the media audiences and the initiators of the information themselves.